Race and risk of maternal vascular malperfusion lesions in the placenta. (September 2018) - Assibey-Mensah, Vanessa; Parks, W. Tony; Gernand, Alison D.; Catov, Janet M.
Abstract: Introduction: The biological mechanisms that underlie racial disparities in placenta-mediated pregnancy complications remain unknown. Placental evidence of maternal vascular malperfusion (MVM), a common pathologic feature of these outcomes, represents hypoxic-ischemic damage to the placenta. We sought to separately estimate the risk of MVM and individual lesions associated with maternal race. Methods: This was a retrospective cohort study of black and white women with singleton live births and placental pathology data at Magee-Womens Hospital during 2008–2012 (n = 15, 581). MVM consisted of ≥1 individual lesions: low placental weight, decidual vasculopathy, accelerated villous maturation, infarcts, and fibrinoid deposition. We separately compared the incidence of MVM and individual lesions in black and white women using logistic regression with generalized estimating equations. Results: After adjusting for covariates, black women had increased risks of MVM (aOR 1.14, 95% CI 1.05–1.23), low placental weight (aOR 1.41, 95% CI 1.28–1.55), and decidual vasculopathy (aOR 1.58, 95% CI 1.36–1.83), also observed in uncomplicated, preterm, and term births. Conversely, black women had decreased risk of infarcts (aOR 0.84, 95% CI 0.75–0.95) compared with white women, also observed in uncomplicated and full-term births. Race was not associated with accelerated villous maturation or fibrinoid deposition. Inverse probability weighting to account for potential selection bias generated similar results. Discussion: Our findings suggest that excess risks of MVM, specifically low placental weight and decidual vasculopathy in black women may be due to a pathological susceptibility to an underlying high-risk vascular phenotype. The clinical significance of race differences in the occurrence of infarcts warrants further investigation. Highlights: Black women have excess risks of low placental weight and decidual vasculopathy. Black women may have pathological susceptibility to a high-risk vascular phenotype. Decreased infarcts in black women warrant further investigation. Placental features may provide insight in risk-stratification of vascular phenotypes. Placentas may reveal race differences in susceptibility to vascular impairments.